Evidence of earlier thyroid dysfunction in newly diagnosed oral lichen planus patients: a hint for endocrinologists. Issue 8 (November 2017) - Arduino, Paolo G; Karimi, Dora; Tirone, Federico; Sciannameo, Veronica; Ricceri, Fulvio; Cabras, Marco; Gambino, Alessio; Conrotto, Davide; Salzano, Stefano; Carbone, Mario; Broccoletti, Roberto
Abstract : The association between oral lichen planus (OLP) and hypothyroidism has been debated with conflicting results: some authors detected a statistically significant association between these two, while others did not confirm it. The aim of this study was to evaluate the thyroid status in patients with newly diagnosed OLP to test the null hypothesis that thyroid disease is not associated with an increased incidence of oral lesions, with a prospective case-control approach. A total of 549 patients have been evaluated, of whom 355 were female. Odds ratio (OR) and 95% confidence intervals (CIs) were obtained. Patients suffering from thyroid diseases were associated with an almost 3-fold increased odds of having OLP (OR 2.85, 95% CI: 1.65–4.94), after adjusting this analysis for age, gender, body mass index, smoking status, diabetes, hypertension and hepatitis C infection. It would be appropriate to further investigate the possible concomitance of OLP among patients with thyroid disorder; endocrinologists should be aware of this association, especially because OLP is considered a potentially malignant oral disorder.